STRATEGY AND MECHANISM OF ENTERPRISES FINANCIAL AND ECONOMIC SECURITY MANAGEMENT IN THE CONDITIONS OF WAR, INDUSTRY 4.0 AND BANI WORLD - Nataliia Zachosova; Dmytro Kutsenko; Oleksii Koval (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The purpose of the research is to establish the characteristic features and signs, the inherent mechanism and strategies of managing financial and economic security, which should be used by domestic enterprises in the war period and in the post-war recovery period in the conditions of the development of Industry 4.0 trends in the realities of the BANI world. Defects in the organization and functioning of the financial and economic security management mechanism were identified, which began to be clearly investigated during the work of business entities in wartime conditions. Additional elements of the financial and economic security management mechanism of the enterprise in the conditions of Industry 4.0 and BANI World are proposed. The peculiarities of the strategy and mechanism of managing the financial and economic security of enterprises in various models of the world system are specified. The outline of the GUARDIAN strategy for the implementation of the tasks of strategic management of the financial and economic security of enterprises was developed and the expediency of its use in the realities of Industry 4.0 and BANI World was substantiated. The development of a new paradigm of strategic management of financial and economic security for the post-war recovery of business entities in the conditions of BANI World, taking into account the trends of the Fourth Industrial Revolution, allows expanding the limits of the application of the tools of effective security-oriented management. In order to successfully optimize traditional approaches to financial and economic security management in the post-war period, it is necessary to transform the financial and economic security management mechanism to ensure its readiness to counteract the impact on the enterprise's corporate resources from the threat of military aggression, global pandemics, the development of the trend of Industry 4.0 and BANI world.